In Memoriam: Charles Wendell Carnahan - Edwin W. Patterson; Stanley M. Rosenblum; Frank P. Aschemeyer; Joseph A. McClain Jr. (Washington University Law Quarterly, 1962)
Charles Wendell Carnahan, 1903-1961. Ph.B. 1923, J.D. 1925, Univ. of Chicago; LL.M. 1937, Juris.Sc.D., 1942, Columbia Univ. Admitted to practice in Illinois, 1925; Missouri, 1943. Engaged in general practice with several law firms and alone, in Chicago, 1925-1930. Asst. Prof. of Law, Univ. of Louisville, 1930-1935; Assoc. Prof. 1935-1936; Prof. of Law 1936-1938; fellow Columbia Univ. 1936-1937; Prof. of Law, Washington Univ. since 1938; Zumbalen Prof. of the Law of Real Property since 1946. Visiting Prof. Univ. of Texas, Summer 1956. Attorney in home-office of General American Life Ins. Co., half-time 1943-1946. Editor, Cases and Materials on Conflict of Laws (1935). Co-Editor (with Taintor, Brown and Harper), Cases and Materials on Conflict of Laws (1950). Author, Conflict of Laws and Life Insurance Contracts (1942), (2d ed. 1958) ; The Dentist and the Law (1955), and of articles in various Law Reviews.
Keywords: Biography; Charles Wendell Carnahan